Functional and genetic diversity changes through time in a cloud forest ant assemblage. (30th October 2020) - Warne, Connor P. K.; Hallwachs, Winnie; Janzen, Daniel H.; Smith, M. Alex
Abstract: Climate change in the Neotropics is causing upslope range shifts. We used arrays of ant species collected in a cloud forest at 1, 500 m in Área de Conservación Guanacaste (ACG), northwestern Costa Rica, collected in two time periods (1998–2000 and 2008–2011) to measure changes in species richness and diversity over a decade. Using metrics of community structure, we found that the species assemblage in the collections from the 1990s was significantly phylogenetically clustered and functionally less diverse as compared to collections from the early 2000s. At both time points, the assemblages were significantly phylogenetically clustered and while the difference in functional diversity between the time points was not significant, the ant assemblage has become lighter in color (on average) over time. When individual species are considered, the overall pattern of replacement is consistent with the cloud forest ant assemblage being colonized by arrivals from lower elevation forests. The invertebrate communities on cloud forested mountain tops are especially vulnerable to a changing climate as there are two factors working together; no higher terrain to which they can move and the invasion of more and more taxa from lower downslope. This vulnerability is already measurable. Abstract : Community of cloud forest ants in ACG has become more diverse, less phylogenetically clustered and lighter in colour through time. This pattern is consistent with cloud forest being colonized by arrivals from lower elevation forests.